A universal way to prepare graphyne derivatives with variable band gap and lithium storage properties. (September 2021) - Yang, Ze; Song, Yuwei; Ren, Xin; Zhang, Chunfang; Hu, Xiuli; Li, Xiaodong; Wang, Kun; Li, Jiazhu; Huang, Changshui
Abstract: As a new carbon allotrope, graphyne (GY) has been predicted with singular and abundant electrochemical capabilities. Although it is difficult to prepare GY directly, the preparation of GY derivatives can help us to understand the properties of GY from another perspective. Herein, we developed a facile strategy to prepare GY derivatives such as nitrogen (N) substituted GYs which are comprised by azaaromatic rings and acetylene bonds. Their band gap and lithium storage properties have been tuned by presetting the number of N atoms in the benzene ring. Both properties and applications of the as-prepared GYs have been studied and compared with the calculation results of GY. With the increase of N content in GY, the charge concentration and the conductivity have been improved, while the band gap has been decreased and lithium storage capability has been enhanced, demonstrating the property and performance of GY can be well regulated by precise N introduction. Notably, all these experimental and theoretical results suggested a universal avenue for the preparation of GY based versatile materials with regulated properties by tuning the composition of benzene rings. Graphical abstract: Image 1